Pengembangan Handout Mata Pelajaran Bahasa Arab Berbasis Cerita Pendek Tematik Untuk Melatih Kemampuan Berpikir Kritis Siswa - Muhammad Arif Nasruddin (Cordova Journal : languages and culture studies, 2020)
The majority of students at Madrasah Ibtidaiyah Al-Mustaqim Lawang Malang still find it difficult to apply thinking skills, this problem the researcher wants to elaborate on by developing Arabic Handout Subjects to Train Students' Critical Thinking Skills. The purpose of this research is to develop Handout for Arabic Subjects based on Thematic Short Stories, Knowing the feasibility of Handout for Arabic Subjects Based on Thematic Short Stories, and Knowing students' critical thinking skills. The method that researchers use is the method of research and development (research and development), with ADDIE design (Analysis, Design, Development, Implementation, Evaluation). The development of this teaching material has resulted in a product in the form of teaching materials for Arabic Subject Handouts based on Thematic Short Stories. From the results of the validation, this Handout is proven valid, with an average of 96% material validation stating very valid and the results of the validation of media experts 94% saying it is very valid, in line with this value the test results for students of Madrasah Ibtidaiyah Al-Mustaqim Lawang show 88, 1% said it was valid, thus the research on the development of Handout for Arabic Subjects based on Thematic Short Stories was effective in improving students' critical thinking skills.